TRPM7 Modulates Human Pancreatic Stellate Cell Activation - Julie Auwercx; Philippe Kischel; Thibaut Lefebvre; Nicolas Jonckheere; Alison Vanlaeys; Stéphanie Guénin; Silviya Radoslavova; Isabelle Van Seuningen; Halima Ouadid-Ahidouch; Hemant M. Kocher; Isabelle Dhennin-Duthille; Mathieu Gautier (Cells, 2022)
Pancreatic diseases, such as pancreatitis or pancreatic ductal adenocarcinoma, are characterized by the presence of activated pancreatic stellate cells (PSCs). These cells represent key actors in the tumor stroma, as they actively participate in disease development and progression: reprograming these PSCs into a quiescent phenotype has even been proposed as a promising strategy for restoring the hallmarks of a healthy pancreas. Since TRPM7 channels have been shown to regulate hepatic stellate cells proliferation and survival, we aimed to study the role of these magnesium channels in PSC activation and proliferation. PS-1 cells (isolated from a healthy pancreas) were used as a model of healthy PSCs: quiescence or activation were induced using all-trans retinoic acid or conditioned media of pancreatic cancer cells, respectively. The role of TRPM7 was studied by RNA silencing or by pharmacological inhibition. TRPM7 expression was found to be correlated with the activation status of PS-1 cells. TRPM7 expression was able to regulate proliferation through modulation of cell cycle regulators and most importantly p53, via the PI3K/Akt pathway, in a magnesium-dependent manner. Finally, the analysis of TCGA database showed the overexpression of TRPM7 in cancer-associated fibroblasts. Taken together, we provide strong evidences that TRPM7 can be considered as a marker of activated PSCs.